Reaksi Pasar Saham terhadap Pengumuman Peluncuran ISSI di Bursa Efek Indonesia (Studi Kasus pada Saham PT Telekomunikasi Indonesia, Tbk) - Dita Roosemella Paramadina; Achmad Helmy Djawahir (Jurnal Ilmiah Mahasiswa FEB, 2012)
This research was based on the announcement of the launch Indonesia Sharia Stock Index (ISSI), which can influence the decisions of investors in the capital market. The purpose of this research to determine how the reaction of investors to the announcement through ISSI stocks in infrastructure, and transportation untilitas listed on the Indonesia Stock Exchange (IDX). This type of research using event study method to determine how the market reaction to the announcement. This study chosed PT Telekomunikasi Indonesia, Tbk  as sample using purposive sampling method. The indicator used are  abnormal return and trading volume activity. Calculation of the data did not find  significant  abnormal return value during window period. The results of calculation showed negative abnormal return value. Through Paired Sample T-test, there was no significant difference in abnormal return before and after the announcement. In the calculation of the volume of trading activity was also not found significant value during the window period. Through Paired Sample T-test, there was no significant differences in the volume of trading activity before and after the announcement. Based on these results concluded that the announcement of the launch of ISSI does not significantly affect the investment decisions of investors and there is an indication that investors still doubt the halal investing in the stock market. Keywords: Abnormal Returns, Trading Volume Activity, Index Announcement, Sharia.